2022
DOI: 10.1021/acscatal.2c02170
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Synergistic Effect in a One-Component Lewis Pair System: Serving as a Dual Initiator and Catalyst in the Ring-Opening Polymerization of Epoxides

Abstract: Ring-opening polymerization (ROP) is a powerful approach to prepare well-defined polymers. Herein, a one-component Lewis pair strategy was adopted, and two delicate Lewis pairs 1–2 were rationally designed and conveniently synthesized. Lewis pairs 1–2 featured an electropositive phosphonium cation, two electrophilic boron centers involving two 9-borabicyclo[3.3.1]­nonane moieties, and a nucleophilic halide (Br– or I–). Lewis pair 1–2-mediated ROP of propylene oxide (PO) exhibited activity (turnover frequency =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…Additionally, we explored epoxides including butylene oxide (BO), n -butyl glycidyl ether (BGE), and 4-vinyl cyclohexene oxide (VCHO). Catalysts [P-C5-BBN 4 ]­[Br] and [P-C5-BBN 4 ]­[NBDC] readily polymerized BO at ambient temperatures in the absence of CO 2 to afford polybutylene ether . However, under 2.76 MPa CO 2 , [P-C5-BBN 4 ]­[Br] selectively produced polybutylene carbonate (Table , entry 1), suggesting that phosphonium borane catalysts can switch between polyether/polycarbonate manifolds.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we explored epoxides including butylene oxide (BO), n -butyl glycidyl ether (BGE), and 4-vinyl cyclohexene oxide (VCHO). Catalysts [P-C5-BBN 4 ]­[Br] and [P-C5-BBN 4 ]­[NBDC] readily polymerized BO at ambient temperatures in the absence of CO 2 to afford polybutylene ether . However, under 2.76 MPa CO 2 , [P-C5-BBN 4 ]­[Br] selectively produced polybutylene carbonate (Table , entry 1), suggesting that phosphonium borane catalysts can switch between polyether/polycarbonate manifolds.…”
Section: Resultsmentioning
confidence: 99%
“…24 What deserves particular attention is the proposed mechanism, which necessitates two equivalents of Et 3 B per organobase, a stoichiometry inherently linked to the simultaneous monomer activation and chain-end deactivation/coordination, which is also well-known from Lewis-pair polymerization (Scheme 1). 25 The viability of using multi-centered, onium-bridged (achiral) boranes for polymerization catalysis has been impressively demonstrated by Wu and others, 26–28 while Du's work highlighted the potential of in situ -formed chiral diboranes for, i.e. , asymmetric imine hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…24 What deserves particular attention is the proposed mechanism, which necessitates two equivalents of Et3B per organobase, a stoichiometry inherently linked to the simultaneous monomer activation and chain-end deactivation/coordination, which is also well-known from Lewis-pair polymerization (Scheme 1). 25 The viability of using multi-centered, onium-bridged (achiral) boranes for polymerization catalysis has been impressively demonstrated by Wu and others, [26][27][28] while Du's work highlighted the potential of in-situ-formed chiral diboranes for, i.e., asymmetric imine hydrogenation. [29][30][31] Herein it will be shown that these characteristics can be exploited further to engender stereoselective polymerization of rac-PO and other epoxides by using simple, chiral diboranes as co-catalysts, notably retaining the benefits of a well-controlled polymerization and a useful tolerance towards polyester-type initiators.…”
Section: Introductionmentioning
confidence: 99%
“…From the examples of highly active metallic catalysts that have been utilized along with transfer agents and the recently developed bifunctional 9-BBN catalysts, , we reasoned that bifunctional organoboron carrying more accessible boron centers than in the BBN case potentially exhibits an even higher reactivity and thus can be used in the presence of transfer agents. Our experience in alkylborane- mediated polymerization showed us that the steric hindrance around boron centers is an important factor affecting the polymerization of epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, water was added as a transfer agent in the ROP of PO catalyzed by one of the 9-BBN bifunctional catalysts recently disclosed to obtain PPO telechelics. 36 A bicomponent TEB system including an initiator was also successfully used in the presence of a small amount of CTA, but in both bicomponent TEB system and 9-BBN bifunctional catalyst cases, it was necessary to use relatively high loading of boron-based catalysts which prevented their industrial implementation. Overall, rare are organocatalysts that are capable of producing both ultrahigh molar mass polyethers and low molar mass polyether telechelics in the presence of a transfer agent.…”
Section: ■ Introductionmentioning
confidence: 99%